TERT promoter mutations and monoallelic activation of TERT in cancer - Huang, F W (Oncogenesis, 2015)
Here we report that promoter mutations in telomerase (TERT), the most common noncoding mutations in cancer, give rise to monoallelic expression of TERT. Through deep RNA sequencing, we find that TERT activation in human cancer cell lines can occur in either mono- or biallelic manner. Without exception, hotspot TERT promoter mutations lead to the re-expression of only one allele, accounting for approximately half of the observed cases of monoallelic TERT expression. Furthermore, we show that monoallelic TERT expression is highly prevalent in certain tumor types and widespread across a broad spectrum of cancers. Taken together, these observations provide insights into the mechanisms of TERT activation and the ramifications of noncoding mutations in cancer.